Effects of melatonin and vitamin C on cigarette smoke-induced damage in the kidney - Ozan, E.; Sonmez, M. F.; Ozan, S.; Colakoglu, N.; Yilmaz, S.; Kuloglu, T. (Sage Publications Inc, 2007)
This study was carried out to investigate smoke-induced structural and biochemical changes and protective effects of co-administered melatonin and vitamin C in the kidney. Twenty-four Wistar adult female rats were used in this study. Animals were divided into four groups. The first group rats were used as control. The second group of rats inhaled cigarette smoke. Smile smoke inhaling third and fourth group rats received melatonin and vitamin C, respectively. At the end of experimental study, kidney tissues and blood samples were taken under ether anesthesia. Tissues were prepared and examined by light microscopy. Malondialdehyde and glutathione levels and catalase activity were determined. By light microscopic observation, a decrease of Bowman space of some renal corpuscles, foamy-like tubules, dilatation and congestion of the peritubuler vessels, and atrophy of the some renal corpuscles were observed in group II. In groups III and IV melatonin and vitamin C relatively protected the kidney tissue against smoke intoxication. Biochemical examination showed that malondialdehyde and glutathione levels and catalase activity in group II were higher than in group I. Melatonin and vitamin C injection to group III and IV caused a decrease in malondialdehyde and glutathione levels. Catalase activity did not change in these groups. We have shown that cigarette smoke inhalation caused structural changes in the kidney. However, melatonin and vitamin C administration produced in some degree protection against smoke-induced damage.
Keywords: Ascorbic-Acid Prophylaxis; Chromosome-Aberrations; Frequency; Assay